Investigation of BaTiO3 and TiO2 Based Nano-fillers on the Space Charge and Electrical Strength of Cross-linked Polyethylene (XLPE) - Rahman A.B.A.; Rahman M.S.A.; Ariffin A.M.; Ali N.H.N.; Ghani A.B.A.; Lau K.Y.; Mohamad M.S.; Osman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aliphatic compounds; Barium titanate; Electric space charge; Fillers; High-k dielectric; Nanocomposites; Oxide minerals; Polyethylenes; Titanium dioxide; Breakdown performance; Breakdown strengths; Crosslinked polyethylene; Dielectric strengths; Electrical applications; Nanocomposite polymers; Nanocomposite samples; Space charge formations; Dielectric materials